Development and application of quadruplex real time quantitative PCR method for differentiation of Muscovy duck parvovirus, Goose parvovirus, Duck circovirus, and Duck adenovirus 3 - Haojie Wang; Jianxing Chen; Tongqing An; Hongyan Chen; Yue Wang; Liangquan Zhu; Changqing Yu; Changyou Xia; He Zhang (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMuscovy duck parvovirus (MDPV), Goose parvovirus (GPV), Duck circovirus, (DuCV) and Duck adenovirus 3 (DAdV-3) are important pathogens that cause high morbidity and mortality in ducks, causing huge economic loss for the duck industry.MethodsThe present study, a quadruplex one-step real time quantitative PCR method for the detection of MDPV, GPV, DuCV, and DAdV-3 was developed. ResultsThe results showed that assay had no cross-reactivity with other poultry pathogens [Duck plague virus (DPV), Duck tembusu virus (DTMUV), H6 avian influenza virus (H6 AIV), New duck reovirus (NDRV), Newcastle disease virus (NDV), H4 avian influenza virus (H4 AIV), Escherichia coli (E. coli), Muscovy duck reovirus (MDRV), Egg drop syndrome virus (EDSV), Pasteurella multocida (P. multocida)]. The sensitivity result showed that the limits of detection for MDPV, GPV, DuCV, and DAdV-3 were 10, 10, 1 and 10 copies/µl, respectively; The coefficients of variation intra- and inter-method was 1-2%; The range of linear (109 to 103 copies/µL) demonstrated the R2 values for MDPV, GPV, DuCV, and DAdV-3 as 0.9975, 0.998, 0.9964, and 0.996, respectively. The quadruplex real time quantitative PCR method efficiency was 90.30%, 101.10%, 90.72%, and 90.57% for MDPV, GPV, DuCV, and DAdV-3, respectively. 396 clinical specimens collected in some duck sausages from June 2022 to July 2023 were simultaneously detected using the established quadruplex real time quantitative PCR method and the reported assays. The detection rates for MDPV, GPV, DuCV, and DAdV-3 were 8.33% (33/396), 17.93% (71/396), 33.58% (133/396), and 29.04% (115/396), respectively. The agreement between these assays was greater than 99.56%.DiscussionThe developed quadruplex real-time quantitative PCR assay can accurately detect these four viruses infecting ducks, providing a rapid, sensitive, specific and accurate technique for clinical testing.